2004
DOI: 10.1029/2003jb002697
|View full text |Cite
|
Sign up to set email alerts
|

Physical balances in subseafloor hydrothermal convection cells

Abstract: [1] We use a simplified model of convection in a porous medium to investigate the balances of mass and energy within a subseafloor hydrothermal convection cell. These balances control the steady state structure of the system and allow scalings for the height, permeability, and residence time of the ''reaction zone'' at the base of the cell to be calculated. The scalings are presented as functions of (1) the temperature T D of the heat source driving the convection and (2) the total power output F U . The model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 45 publications
4
80
0
Order By: Relevance
“…This was initially suggested by Edward Lorenz [70], and is closely related to the hypothesis formulated by Paltridge [71,13,72] that the atmospheric circulation maximizes entropy production. Since then, further work has shown that MEP yields reasonable predictions of hemispheric heat transport on other planetary bodies [14,73] and of empirical friction coefficients in atmospheric general circulation models [15,74], but also for vertical convection [71,75,49,37,51,76] and convection at hydrothermal vents at the seafloor [77]. More support comes from studies of turbulence and its effects on heat transport and entropy production [78][79][80][81][82].…”
Section: Maximizing Power Generation and Transfermentioning
confidence: 98%
“…This was initially suggested by Edward Lorenz [70], and is closely related to the hypothesis formulated by Paltridge [71,13,72] that the atmospheric circulation maximizes entropy production. Since then, further work has shown that MEP yields reasonable predictions of hemispheric heat transport on other planetary bodies [14,73] and of empirical friction coefficients in atmospheric general circulation models [15,74], but also for vertical convection [71,75,49,37,51,76] and convection at hydrothermal vents at the seafloor [77]. More support comes from studies of turbulence and its effects on heat transport and entropy production [78][79][80][81][82].…”
Section: Maximizing Power Generation and Transfermentioning
confidence: 98%
“…A number of studies have dealt with various aspects of this theme (e.g., Cathles 1993;Jupp andSchultz 2000, 2004). The basic principle is rather simple: if the fl uid fl ows too fast, it will stay relatively cold since the heat supply cannot keep pace; if the fl uid fl ows very slowly, heat transfer to the fl uid will be optimized.…”
Section: Permeability Discharge Recharge and Effi Ciency Of Heat Trmentioning
confidence: 99%
“…The fully fluid-saturated model domain is initialized with seawater salinity, a geothermal gradient of ∼20 • C km −1 for old oceanic crust (which relates to a basal heat flux of Q c = 0.045 W m −2 applied to the bottom boundary), and the corresponding hydrostatic pressure. The host rock has a porosity of φ = 0.1, a homogeneous permeability of k = 10 −14 m 2 (a value typically assumed for hydrothermal convection in oceanic crust, e.g., Jupp and Schultz, 2004), a thermal conductivity of K = 2 W m −1 • C −1 , a heat capacity of the rock of c pr = 880 J kg −1 • C −1 , and a density of the solid rock matrix of ρ r = 2700 kg m −3 . The values correspond to the conditions used in comparable hydrothermal simulation projects (e.g., Hayba and Ingebritsen, 1997).…”
Section: The Darcy Velocity Vectormentioning
confidence: 99%